2008
DOI: 10.2310/7290.2008.00015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dose Response in Chronic Doxorubicin-Mediated Cell Death with Cardiac Technetium 99m Annexin V Single-Photon Emission Computed Tomography

Abstract: The aim of this study was to evaluate whether technetium 99m hydrazinonicotinamide (99mTc-HYNIC)-annexin V single-photon emission computed tomography (SPECT) would detect dose-dependent doxorubicin (DOX)-mediated cell death in the heart compared with functional echocardiography. Adult female Sprague-Dawley rats were treated with DOX (cumulative dose of 15 or 7.5 mg/kg) or saline (n = 7) and monitored by echocardiography. Rats were injected with 7 to 8 mCi 99mTc-HYNIC-annexin V and imaged 1 hour postinjection u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…The mouse was euthanized 1 h post-injection and then imaged using one-, four-, and five-pinhole configurations under the same acquisition time, i.e., ∼130 min, eliminating the respiratory and cardiac motion artifacts to demonstrate the best achievable resolution for this system. To demonstrate the effectiveness of this system for other more common application, which was mostly available for our study, i.e., cardiac imaging in live animals, we then imaged the anesthetized doxorubicin-induced cardiotoxicity rat model [27] and its corresponding saline control, with body diameters of ∼5 cm under the same acquisition time of ∼64 min. The rats were injected with ∼8 mCi 99m Tc labeled Annexin V to target the apoptotic cells in the heart.…”
Section: Evaluation Of the Collimator By Physical Phantoms And Animalmentioning
confidence: 99%
“…The mouse was euthanized 1 h post-injection and then imaged using one-, four-, and five-pinhole configurations under the same acquisition time, i.e., ∼130 min, eliminating the respiratory and cardiac motion artifacts to demonstrate the best achievable resolution for this system. To demonstrate the effectiveness of this system for other more common application, which was mostly available for our study, i.e., cardiac imaging in live animals, we then imaged the anesthetized doxorubicin-induced cardiotoxicity rat model [27] and its corresponding saline control, with body diameters of ∼5 cm under the same acquisition time of ∼64 min. The rats were injected with ∼8 mCi 99m Tc labeled Annexin V to target the apoptotic cells in the heart.…”
Section: Evaluation Of the Collimator By Physical Phantoms And Animalmentioning
confidence: 99%
“…Targeted molecular imaging with SPECT, PET, or MRI may be able to detect cell death due to doxorubicin 25 and to detect subclinical cardiotoxicity.…”
Section: Imaging To Detect Cardiotoxicitymentioning
confidence: 99%
“…Another study with doxorubicin treated rats (cumulative dose: 7.5mg/Kg and 15mg/Kg) demonstrated that dose dependent increase in 99m Tc-annexin V uptake by SPECT/CT and TUNEL positivity. In contrast in this syudy, echocardiography detected ventricular dysfunction only at the highest doxorubicin dose ( Gabrielson, et al, 2008). These data suggest that apoptosis imaging could serve as a more sensitive early marker of doxorubicin cardiotoxixity than left ventricular dysfunction, might providing the opportunity to modify or stop the chemotherapy before clinically overt heart failure.…”
Section: Apoptosis Imaging In Cardiotoxicity Induced By Chemotherapymentioning
confidence: 39%